MRI-compatible breast/rib phantom for evaluating ultrasonic thermal exposures - Menikou, Georgios; Yiannakou, Marinos; Yiallouras, Christos; Ioannides, Cleanthis; Damianou, Christakis A. (My University, 2018)
Introduction: The target of this study was the development of a magnetic resonance imaging (MRI) compatible breast phantom for focused ultrasound which includes plastic (ABS) ribs. The objective of the current study was the evaluation of a focused ultrasound procedure using the proposed phantom that eliminates rib heating. Material and Methods: The proposed phantom was evaluated using two different focused ultrasound exposures. The surrounding breast tissue was mimicked using an agar–silica–evaporation milk gel (2% w/v – 2% w/v – 40% v/v). Results: The attenuation of the ABS was similar to that of ribs. MR thermometry of focused ultrasound exposures were acquired using the breast/rib phantom. In one exposure focused ultrasound was applied with far-field targeting of the ribs. In the other exposure, the transducer was positioned laterally, thus avoiding exposure of the rib to focused ultrasound. Conclusions: Due to growing interest in using MRI guided focused ultrasound (MRgFUS) for patients with breast cancer, the proposed breast/rib phantom can be utilized as a very useful tool for evaluating ultrasonic protocols.
Keywords: Breast; Cancer; MRI; Rib; Ultrasound